Bohemian Luxury Style in the Interior Design of a Coffee House and Barista Training - Septiana Trisnawati; Rahmanu Widayat (Pendhapa, 2021)
This Bohemian Luxury Coffee House Interior Design and Barista Training aims to (1) produce a coffee house interior design that is able to fulfil commercial, educational, and entertainment functions. (2) Providing interior design for a coffee house with a bohemian luxury style. The method used in this research is programming, including literature study, survey, and interview. Then data analysis, development of ideas, and design methods. From this analysis, it can be concluded several things (1) The interior design of the Coffee House and Barista Training as a solution for coffee lovers to gather and share knowledge about the types of coffee or the correct coffee making (2) Shapes, colours and materials applied according to with the theme of bohemian luxury in all interior elements. (3) The atmosphere of the space that is raised is a relaxed, comfortable, and elegant atmosphere.